The gently bowing person: an ideal among the Yupno in Papua New Guinea - Wassmann, Jürg (Heidelberg Studies in Pacific Anthropology, 2016)
Cover -- Title Page -- Copyright -- Contents -- List of Illustrations -- Maps -- Beg. 1: The Finisterre Range -- Beg. 2: Mentioned languages between 1873 and 1907 -- Beg. 3: Newly mentioned languages between 1947 and 1959 -- Beg. 4: Newly mentioned languages between 1960 and 1975 -- 1.1: The Yupno Valley -- 1.2: "Kokop kirat" flying in -- 5.1: Yupno Valley -- Figures -- 2.1: Body counting system (by Paul Yanu) -- 2.2: Yamane's relatives -- 3.1: "Koñgap" sung in Gua 1 -- 3.2: "Nsaguo" feather wheel (by Paul Yanu) in the middle of the book, "see" illustration 3 -- 3.3: Kuval kalda: One possible interpretation -- 3.4: Musical notation of a "koñgap", Seiten: 142-143 -- 3.5: Zaka sings Faiu -- 3.6: Zaka sings Faiu - long version -- 3.7: Erap sings Faiu -- 3.8: Erap sings Faiu - long nucleus -- 4.1: Sorting task: The system of the presented objects -- 4.2: The results of the sorting task -- 5.1: The coordinating system according to Danda's earth drawing -- 5.2: Schematic drawing -- 5.3: The structure of a house (by Paul Yanu -- 5.4: Schematic drawing showing the two houses used in the study -- 5.5: Worlds in mind, Seiten: 213-215 -- 5.6: Drawing according to map from Tapen to Urop -- 5.7: Drawing by Sivik -- 6.1: Transcription sheet for Steve's maze -- 6.2: The topography of the upper Yupno Valley (surrounding Gua village, cf. Núñez et al. 2012a: 30) -- End 1: From drawing 5.4, worlds in mind -- End 2: The order of foodstuff presented in sorting task (cf. Figure 4.1) -- Illustrations -- Black and white pictures within the text -- 1.3: Ponds for the deluge of the neighbouring Wantoat (Vial1938a: 41) -- 1.6: The missionaries' conference 1910 (kindly provided by Archiv Mission EineWelt) -- 1.7: Yapit, the first Yupno evangelist (kindly provided by Archiv Mission EineWelt) -- 3.1: Gua 1, 2005 -- 3.4: "Kuval kalda", 1988 -- 5.2: A Yupno house.